(untitled) (Janaki Medical College Journal of Medical Science, 2025)
Background & Objectives: Antenatal care is special care given to women during pregnancy and is regarded as a cornerstone for improving perinatal outcomes. In Nepal, men are the backbone of the family, and their engagement in maternal health care is crucial for promoting maternal and fetal health. The objective of this study was to find out the husband’s involvement in the care of antenatal women, which includes support and help in providing a nutritious diet, rest and sleep, help in household chores, attending antenatal clinic, and planning for birth preparedness. Materials and Methods: A descriptive cross-sectional design was used. All the pregnant women in the third trimester visiting the ANC Clinic in Rapti Academy of Health Science, Dang, were the study population. The structured interview schedule was used for the data collection. Data was entered in Statistical Package for Social Science (SPSS) and was analyzed using descriptive and inferential statistics. Results: This study’s finding shows that most pregnant women’s husbands (76%) had high involvement in antenatal care. There was a statistically significant association between the level of the husband’s participation in antenatal care and the age of the respondent (P value <0.05). Conclusions: The majority of the respondent had high involvement of their husband in antenatal care, but involvement in birth preparedness and complication readiness was quite low; therefore, awareness program on birth preparedness and complication readiness is recommended.